2012
DOI: 10.1093/eurheartj/ehs005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins on ventricular tachyarrhythmia, cardiac arrest, and sudden cardiac death: a meta-analysis of published and unpublished evidence from randomized trials

Abstract: Statins have a modest beneficial effect on sudden cardiac death. However, previous suggestions of a substantial protective effect on ventricular arrhythmic events could not be supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 73 publications
0
30
0
3
Order By: Relevance
“…This finding is consistent with the effectiveness of preventative therapies, particularly statins and angiotensinconverting enzyme inhibitors, in reducing the long-term risk of myocardial infarction and sudden death in patients with established coronary disease. [21][22][23][24][25][26] The time periods in this study corresponded approximately with balloon angioplasty (early provisional stenting, [1991][1992][1993][1994][1995][1996] as the primary interventional approach, routine bare-metal stent (1997)(1998)(1999)(2000)(2001)(2002), and routine drug-eluting stent placement (2003)(2004)(2005)(2006)(2007)(2008). 27 Randomized studies have failed to show a long-term mortality advantage of bare metal stents over balloon angioplasty or of drug-eluting stents over bare-metal stents in multiple clinical settings.…”
Section: Decline In Cardiac Mortalitymentioning
confidence: 99%
“…This finding is consistent with the effectiveness of preventative therapies, particularly statins and angiotensinconverting enzyme inhibitors, in reducing the long-term risk of myocardial infarction and sudden death in patients with established coronary disease. [21][22][23][24][25][26] The time periods in this study corresponded approximately with balloon angioplasty (early provisional stenting, [1991][1992][1993][1994][1995][1996] as the primary interventional approach, routine bare-metal stent (1997)(1998)(1999)(2000)(2001)(2002), and routine drug-eluting stent placement (2003)(2004)(2005)(2006)(2007)(2008). 27 Randomized studies have failed to show a long-term mortality advantage of bare metal stents over balloon angioplasty or of drug-eluting stents over bare-metal stents in multiple clinical settings.…”
Section: Decline In Cardiac Mortalitymentioning
confidence: 99%
“…Possible mechanisms which could explain the antiarrhythmic properties might involve the capacity of statins for NO-dependent endothelial function regulation, inflammation and oxidative stress reduction, highrisk plaque rupture and ischemia/reperfusion myocardial injury prevention, improvement in heart rate variability and decreased QT dispersion [14,22] . Recently Rahimi et al (2012) in a meta-analysis of 29 RCTs concluded that statin therapy did not significantly reduce the risk of ventricular tachyarrhythmia and cardiac arrest, but was responsible for a significant 10% reduction in SCDs [23] . The results of that study indicated that statin therapy is highly unlikely to have a beneficial effect on the prevention of ventricular arrhythmias.…”
Section: Statin Therapy and Scdmentioning
confidence: 99%
“…The results of that study indicated that statin therapy is highly unlikely to have a beneficial effect on the prevention of ventricular arrhythmias. The authors concluded that reduction of the risk of sudden cardiac death was associated with the reduction of LDL cholesterol by statin [23] . On the other hand, large-scale RCTs -the Controlled Rosuvastatin Multinational Trial in Heart Failure (CORONA) [24] and the Effect of rosuvastatin in patients with chronic heart failure (GISSI-HF) [25] -showed no association between rosuvastatin therapy at a low dose and reduction in mortality from any cause.…”
Section: Statin Therapy and Scdmentioning
confidence: 99%
“…Крупный метаанализ, прове-денный в 2005 г., который включал 90 тыс. па-циентов, принимавших участие в 14 рандоми-зированных исследованиях, убедительно доказал эффективность статинов для профи-лактики ВСС у больных ИБС [19]. Прием стати-нов для профилактики развития сердечно-сосу-дистых осложнений рекомендуется всем боль-ным, относящимся к группе высокого сердечно-сосудистого риска.…”
Section: статиныunclassified